Guideline Adherence of β-blocker Initiating Dose and its Consequence in Hospitalized Patients With Heart Failure With Reduced Ejection Fraction - Zhou, Yiling; Zeng, Yuping; Wang, Si; Li, Nan; Wang, Miye; Mordi, Ify R.; Ren, Yan; Zhou, Youlian; Zhu, Ye; Tian, Haoming; Sun, Xin; Chen, Xiaoping; et al. (Frontiers in Pharmacology, 2021)
Background: We aim to investigate the guideline adherence of β-blocker (BB) initiating dose in Chinese hospitalized patients with heart failure with reduced ejection fraction (HFrEF) and whether the adherence affected the in-hospital outcomes. Methods: This was a retrospective study of patients hospitalized with HFrEF who had initiated BBs during their hospitalization. We defined adherence to clinical practice guidelines as initiating BB with standard dose and non-adherence to guidelines if otherwise, and examined the association between adherence to guidelines and in-hospital BB-related adverse events. Subgroup analyses based on sex, age, coronary heart disease, and hypertension were performed. Results: Among 1,104 patients with HFrEF initiating BBs during hospitalization (median length of hospitalization, 12 days), 304 (27.5%) patients received BB with non-adherent initiating dose. This non-adherence was related to a higher risk (hazard ratio [95% confidence interval]) of BB dose reduction or withdrawal (1.78 [1.42 to 2.22], P<0.001), but not significantly associated with risks of profound bradycardia, hypotension, cardiogenic shock requiring intravenous inotropes, and severe bronchospasm requiring intravenous steroid during hospitalization. Conclusion: This study identified that over a fourth of patients had received BBs with an initiating dose that was not adherent to guidelines in Chinese hospitalized patients with HFrEF, and this non-adherence is associated with BB dose reduction or withdrawal during hospitalization